The U.S. Experience with No-Fault Automobile Insurance A Retrospective - Anderson, James M. (RAND Corporation, 2010)
No-fault regimes, a formerly popular alternative to the tort compensation system for auto-accident victims, have gradually lost support. Over time, premiums and claim costs have grown in no-fault states relative to other states, primarily driven by explosive medical cost increases. No-fault and tort states have also converged across many domains affecting costs, including excess claiming, litigation patterns, and noneconomic-damage payments.